ANALISIS PENDAPATAN USAHATANI BUNGA MELATI (Jasminum sambac) DI KABUPATEN BATANG PROVINSI JAWA TENGAH - Tiara Intan Palupi; Edy Prasetyo; Mukson Mukson (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2019)
Jasmine is a type of floriculture plant, that is white and has a very fragrant aroma. Jasmine flowers are widely used for activities related to customs as well as industrial raw materials. The use of jasmine is increasingly decreasing because many industries use the essence of jasmine because they are cheaper. The selling price of jasmine flowers tends to fluctuate because the production of jasmine is determined by the season and requests for certain festivals and ceremonies. The purpose of this study was to analyze the income of jasmine flower farmers and analyze the factors that influence the income of jasmine flower farming. The research was carried out in September 2018 in Batang District and Kandeman District, Batang Regency. The research method uses survey methods and data collection methods through interviews. The method for taking samples using Slovin techniques, determining the number of each sub-district using proportional allocation. Methods of data analysis using income analysis, multiple linear regression test and one sample t-test. The results showed that the income of jasmine flower farmers was Rp. 3,330,909 / 0.51 ha / month. The results of the analysis of one sample t-test show that the income of jasmine flower farmers is greater than the District Minimum Wage (UMK). Factors of seed costs, pesticide costs, fertilizer costs, selling prices and labor costs have an effect on simultaneously or partially on the income of jasmine flower farmers.